The Translation Analysis of Religious Terms In “The Alchemist” - Kursiyanto, Shelya Alfani (Institut Agama Islam Negeri Palopo, 2025)
This study examines the translation of religious terms in The Alchemist from English to Indonesian, focusing on the translation procedures applied to these terms. This is a qualitative descriptive study that uses The Alchemist as the primary data source, both in its original English version and Indonesian translation. This research is conducted with two main objectives: (1) to identify the religious terms present in the original English version of The Alchemist, and (2) to examine the translation strategies used to convey these religious terms into Indonesian and evaluate how well the translations maintain the original meaning of the religious terms. Data were collected using document analysis to identify religious terms and analyze how they are translated. Using Peter Newmark’s translation theory, this study shows the eight translation procedures applied in translating religious terms, including through-translation, naturalization, cultural equivalence, functional equivalent, transference, shift or transpositions, synonymy, and recognized translation. A total of 28 religious terms were found, covering references to Islam, Christianity/Catholicism, Judaism, and general or multiple religious concepts. By applying Peter Newmark’s translation procedures, this study explores how translators maintain the essence of religious texts while adapting them to the target audience’s cultural background, contributing to the study of religious term translation.